La vie amère de Maxime Gorki - Alexinsky, Grégoire (Grenoble : Arthaud, 1950)
Bibliotheek Camille Huysmans
Dedicator: Alexinsky, Grégoire, dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: Gorki, Maxim; biografieën; Rusland